diff --git a/src/backend/statistics/README.dependencies b/src/backend/statistics/README.dependencies index 59f9d57..d10e4d0 100644 --- a/src/backend/statistics/README.dependencies +++ b/src/backend/statistics/README.dependencies @@ -90,7 +90,7 @@ Where 'd' is the degree of functional dependence (a=>b). With more than two equality clauses, this process happens recursively. For example for (a,b,c) we first use (a,b=>c) to break the computation into - P(a=?,b=?,c=?) = P(a=?,b=?) * (d + (1-d)*P(b=?)) + P(a=?,b=?,c=?) = P(a=?,b=?) * (d + (1-d) * P(c=?)) and then apply (a=>b) the same way on P(a=?,b=?).